Government House, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (James Book Store, 2009)
A picture of the long driveway with well kept lawn and a variety of tropical plants on both sides, leading to Government House main building and in the background is the St. Ann's Hills. Postcard number 35.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; President's House, The